(untitled) (Research, Society and Development, 2020)
The male artistic gymnastics team in Brazil has achieved expressive results in international events in recent years. Based on the assumption that funding is one of the main pillars for a nation’s sports development, this article sought to describe, from the athletes’ discourse, the financial support received by Brazilian gymnasts during their sports trajectories. To this end, the five gymnasts who represented Brazil in the world championships of the Olympic cycle for the Tokyo Games were interviewed. The content analysis revealed that the beginning of the career was permeated by financial difficulties; the Bolsa-Atleta Program and the High-Performance Athletes Program are the main actions of the federal government that support sport; the Brazilian Gymnastics Confederation makes the costs of travel and salaries feasible to the main athletes, through some partnerships; some clubs offer salaries to ready athletes; the private sector invests individually and on time. It was possible to identify that there is an overlap of actions for the financing of the high-performance athlete in the country.